Nathan F. Twining papers - Twining, Nathan F. (Nathan Farragut), 1897-1982.
Correspondence, diaries, logs, speeches, statements, biographical material, certificates, flight records, newspaper clippings, printed matter, and other papers relating to Twining's role as vice chief and chief of staff of the U.S. Air Force and chairman of the Joint Chiefs of Staff. Correspondents include Omar Nelson Bradley, Travis Bryan, W. Barton Leach, Lauris Norstad, and Charles Erwin Wilson.
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
U.S. Army and Air Force officer; later, publishing company executive.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bradley, Omar Nelson, -- 1893-1981 -- Correspondence; Bryan, Travis, -- 1893- -- Correspondence; Leach, W. Barton -- 1900-1971 -- Correspondence; Norstad, Lauris, -- 1907-1988 -- Correspondence; Wilson, Charles Erwin, -- 1890-1961 -- Correspondence; United States. -- Air Force; United States. -- Air Force. -- Office of the Chief of Staff; United States. -- Air Force. -- Office of the Vice Chief of Staff; United States. -- Joint Chiefs of Staff; Air Force officers; Army officers; Executives